PDK1 is a Regulator of Epidermal Differentiation that Activates and Organizes Asymmetric Cell Division - Dainichi, Teruki (Cell Rep, 2016)
Asymmetric cell division (ACD) in a perpendicular orientation promotes cell differentiation and organizes the stratified epithelium. However, the upstream cues regulating ACD have not been identified. Here we report that phosphoinositide-dependent kinase 1 (PDK1) plays a critical role in establishing ACD in the epithelium. Production of phosphatidylinositol triphosphate (PIP(3)) is localized to the apical side of basal cells. Asymmetric recruitment of atypical protein kinase C (aPKC), and partitioning defective (PAR) 3, are impaired in PDK1 conditional knockout (CKO) epidermis. PDK1(CKO) keratinocytes do not undergo calcium-induced activation of aPKC or IGF1-induced activation of AKT and fail to differentiate. PDK1(CKO) epidermis shows decreased expression of Notch, a downstream effector of ACD, and restoration of Notch rescues defective expression of differentiation-induced Notch targets in vitro. We therefore propose that PDK1 signaling regulates the basal-to-suprabasal switch in developing epidermis by acting as both an activator and organizer of ACD and the Notch-dependent differentiation program.